(untitled) (Research, Society and Development, 2021)
This article has as theme Early Childhood Education: the playful according to the Common National Curriculum Base, in the pre-school stage. This is a field research carried out with 10 teachers from a public school in the northeast region of Brazil, carried out through a questionnaire, having as theoretical bases the Common National Curriculum Base and renowned authors who discuss the subject (literature research) . The objective of this research is to reflect on the relevance of playfulness, illuminated by the Common National Curriculum Base, in the pre-school stage (4 to 5 years and 11 months), in the view of public school teachers in a city in the northeast of Brazil. It is observed from the answers of the interviewed teachers that a part of them had no interest in reading the BNCC to get to know the referred document. Most teachers believe that working with playfulness is the key to teaching with meaningful learning while a part does not want to leave the sameness, wanting to continue in the traditional methodology which they already work on time. It can also be noted that the BNCC subsidizes the teaching of Early Childhood Education through playfulness, with games and games making children learn in a dynamic, meaningful and attractive way.